Conducting a “DEI Audit” of the Academy of Homiletics: Overview of Teaching and Research Practices, 2017-2022 (Homiletic, 2025)
In 2019, the Academy of Homiletics (AoH) launched a multi-year effort to understand and deconstruct the ways that whiteness has systematically impacted the research, practices, and teaching of preaching. In 2022, the AoH received a grant from the Wabash Center for Teaching and Learning in Theology and Religion to study its efforts to “unmask homiletical whiteness” and embrace diversity, equity, and inclusion (DEI) in homiletical pedagogy, research, and scholarship. The first part of this article shares general findings from the survey distributed to 81 members, gauging their attitudes, intentions, and practices regarding DEI. The second part reports on the team’s analysis of 179 syllabi submitted by members from before and after 2019 to track changes in pedagogy regarding DEI. In this “DEI audit,” we note correlations between increased sensitivity to and engagement with DEI while also pointing to differences according to the demographic intersections of members and the topics of interest.